B Cell Depletion and SARS‐CoV‐2 Vaccine Responses in Neuroimmunologic Patients. Issue 3 (8th February 2022) - Kornek, Barbara; Leutmezer, Fritz; Rommer, Paulus S.; Koblischke, Maximilian; Schneider, Lisa; Haslacher, Helmuth; Thalhammer, Renate; Zimprich, Fritz; Zulehner, Gudrun; Bsteh, Gabriel; Dal‐Bianco, Assunta; Rinner, Walter; et al.
Abstract : Objective: The study was undertaken to assess the impact of B cell depletion on humoral and cellular immune responses to severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) vaccination in patients with various neuroimmunologic disorders on anti‐CD20 therapy. This included an analysis of the T cell vaccine response to the SARS‐CoV‐2 Delta variant. Methods: We investigated prospectively humoral and cellular responses to SARS‐CoV‐2 mRNA vaccination in 82 patients with neuroimmunologic disorders on anti‐CD20 therapy and 82 age‐ and sex‐matched healthy controls. For quantification of antibodies, the Elecsys anti‐SARS‐CoV‐2 viral spike (S) immunoassay against the receptor‐binding domain (RBD) was used. IFN‐gamma enzyme‐linked immunosorbent spot assays were performed to assess T cell responses against the SARS‐CoV‐2 Wuhan strain and the Delta variant. Results: SARS‐CoV‐2‐specific antibodies were found less frequently in patients (70% [57/82]) compared with controls (82/82 [100%], p  < 0.001). In patients without detectable B cells (<1 B cell/mcl), seroconversion rates and antibody levels were lower compared to nondepleted (≥1 B cell/mcl) patients ( p  < 0.001). B cell levels ≥1 cell/mcl were sufficient to induce seroconversion in our cohort of anti‐CD20 treated patients. In contrast to the antibody response, the T‐cell response against the Wuhan strain and the Delta variant was more pronounced in frequency ( p  < 0.05) and magnitude ( p  < 0.01) in B‐cell depleted compared to nondepleted patients. Interpretation: Antibody responses to SARS‐CoV‐2 mRNA vaccinnation can be attained in patients on anti‐CD20 therapy by the onset of B cell repopulation. In the absence of B cells, a strong T cell response is generated which may help to protect against severe coronavirus disease 2019 (COVID‐19) in this high‐risk population. ANN NEUROL 2022;91:342–352